Clinical comparative analysis of various duodenal diseases in different age groups - Zhao, Jin; Li, Xuelian; Liu, Qi; Shi, Linyan; Zhang, Ling; Yang, Hong; Zhang, Qianqian (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To investigate differences and relevance of various common duodenal diseases in different parts in the aspects of age, gender, helicobacter pylori (H.pylori) infection, application of non-steroidal anti-inflammatory drugs (NSAIDs), smoking, or drinking. Materials and Methods: the medical records of various duodenal diseases were collected and tested for difference using the 2 test or Fisher exact probability method. Results: (1) the proportions of Duodenal ulcer (DU), inflammation, and duodenal bulb diseases in the adult group (A) (47.98%, 36.70%, 66.63%) were higher than the elderly group (E) (41.38%, 29.83%, 56.82%), but the proportions of duodenal diverticulum (DD), tumor, diseases in the descending and ascending segments (2.95%, 1.43%, 9.14%, 0.14%) were lower than Group E (13.73%, 3.69%, 19.41%, 0.76%) (P < 0.001). (2) The positive rate of H.pylori (63.64%) in the duodenal bulb diseases was higher than the bulb-descending segment (53.75%), but the application rate of NSAIDs (16.44%) in the duodenal bulb-descending diseases was lower than the descending segment (24.81%) (P<0.001). Conclusions: (1) DU, inflammation, and duodenal bulb diseases are common in adults, but DD, tumor, diseases in the descending and ascending segments are more common in the elderly. (2) Compared with duodenal bulb-descending diseases, the application of NSAIDs has greater impact on the diseases in the descending segment, and the rate of H. pylori infection is higher in duodenal bulb diseases.